2010
DOI: 10.1111/j.1365-2982.2010.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal-specific anxiety: an important factor for severity of GI symptoms and quality of life in IBS

Abstract: Gastrointestinal-specific anxiety seems to be an important factor for GI symptom severity and QOL in patients with IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
131
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(158 citation statements)
references
References 49 publications
14
131
1
7
Order By: Relevance
“…Anxiety, depression, and somatization are more prevalent in IBS patients. Jerndal et al (2010) found that anxiety, which is an important mediating factor, greatly affects the severity of symptoms and QOL, and that reduction of anxiety can achieve a general improvement in IBS symptoms. Two recent studies concluded that depression and somatization were independently associated with IBS (Nicholl et al, 2008;Savas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety, depression, and somatization are more prevalent in IBS patients. Jerndal et al (2010) found that anxiety, which is an important mediating factor, greatly affects the severity of symptoms and QOL, and that reduction of anxiety can achieve a general improvement in IBS symptoms. Two recent studies concluded that depression and somatization were independently associated with IBS (Nicholl et al, 2008;Savas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Previously, it has been reported that nursing professionals who participate in a rotating shift schedule are at a higher risk of psychosocial problems than are those who work the day shift. 18 However, the role of psychosocial risk in shift-working professionals in the development of FGIDs remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The baseline characteristics of included studies are shown in Table 1 22,29 Sphere score in 1 study, 24 and the Beck Anxiety Inventory (BAI) in 1 study. 30 …”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…2B). 11,13,22,25,28,29,34,36 However, 4 of 8 outlier studies were age-sex (hyphen) unmatched. 13,28,29,34 The Anxiety Level in Irritable Bowel Syndrome Patients…”
Section: The Depression Level In Irritable Bowel Syndrome Patientsmentioning
confidence: 99%